Karakteristik Seorang Pengkhotbah Menurut I Timotius 3:1-7 - Otniel Pratama Siagian; Hariyanto Hariyanto; Mulyani Susana; Daud Margiat; Ronio Otniel Panggabean (Anoteros: Jurnal Teologi, 2025)
Preachers play a central role in church life because through their sermons, God's Word is proclaimed and applied to the congregation. However, modern challenges have given rise to a character crisis among preachers, resulting in a decline in the quality of their preaching and the growth of their congregation's faith. This study aims to examine the characteristics of biblical preachers based on 1 Timothy 3:1–7 and analyze their influence on the effectiveness of their ministry. This study used a qualitative method with a literature approach through the study of the Bible, relevant books, and theological journals. The results indicate that the characteristics of preachers according to 1 Timothy 3:1–7 include living a morally blameless life, being competent to teach, not being a lover of money, being faithful in marriage, being spiritually mature, having self-control, and having a good testimony. These characteristics serve as important normative standards for restoring the quality of church ministry and the growth of their congregation's faith. Pengkhotbah memiliki peran sentral dalam kehidupan gereja karena melalui khotbah Firman Tuhan diberitakan dan diaplikasikan bagi jemaat. Namun, tantangan zaman modern telah memunculkan krisis karakter di kalangan pengkhotbah yang berdampak pada menurunnya kualitas pelayanan khotbah dan pertumbuhan iman jemaat. Penelitian ini bertujuan mengkaji karakteristik pengkhotbah yang Alkitabiah berdasarkan I Timotius 3:1–7 serta menganalisis pengaruhnya terhadap efektivitas pelayanan Firman. Penelitian ini menggunakan metode kualitatif dengan pendekatan kepustakaan melalui studi Alkitab, buku, dan jurnal teologi yang relevan. Hasil kajian menunjukkan bahwa karakteristik pengkhotbah menurut I Timotius 3:1–7 meliputi hidup tidak bercacat secara moral, cakap mengajar, tidak hamba uang, setia dalam pernikahan, dewasa rohani, berpenguasaan diri, dan memiliki kesaksian yang baik. Karakter tersebut menjadi standar normatif yang penting bagi pemulihan kualitas pelayanan gereja dan pertumbuhan iman jemaat.